STUNTING REDUCTION ACCELERATION POLICY IN INDONESIA: POLITICAL ANALYSIS AND THE ROLE OF THE MINISTRY OF POPULATION AND FAMILY DEVELOPMENT - Khairudin Gustam; Usni (Universitas Muhammadiyah Jakarta, 2026)
Stunting is a strategic issue in human development in Indonesia that is not only related to health aspects, but also reflects structural problems in public policy governance. Although the government has established Presidential Regulation Number 72 of 2021 concerning Stunting Reduction Acceleration as a form of national political commitment, the stunting prevalence achievement by 2024 has not fully reached the target. The Ministry of Population and Family Planning has a central role as the coordinator of cross-sectoral policy implementation, both at the central and regional levels. This study aims to analyze the policy of accelerating stunting reduction in the framework of public policy politics and to examine the role of the ministry in cross-sectoral coordination and center-regional relations. This research uses a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews and documentation studies. Data analysis was carried out by examining the dynamics of policy implementation using the perspective of policy implementation theory, political will, and collaborative governance. The results showed that the government showed strong commitment (Political Will) through policy initiatives, budget priorities, and mobilization of support. However, there is still a need for improvement in law enforcement and business sustainability. Penta Helix collaboration (Collaborative Governance) between government, private sector, community, mass media, and academia is also needed to improve access to health, nutrition, and education services. The recommendations of this study include: (1) strengthening policy implementation with effective coordination; (2) increasing government commitment; (3) fulfilling the dimensions of political commitment; and (4) expanding Penta Helix collaboration. This research contributes theoretically to the development of public policy politics studies and practically becomes an evaluation material for strengthening the governance of stunting reduction acceleration policies in Indonesia.